EFISIENSI PASIR KUARSA DESA SUAK PUTAT,DESA PARIT DAN DESA TANJUNG HARAPAN KABUPATEN MUARO JAMBI DALAM MENURUNKAN PARAMETER PENCEMAR AIR SUNGAI BATANGHARI - Siti Umi Kalsum; Suandana Suandana; Yunizar Yunizar (Universitas Batanghari Jambi, 2015)
Batanghari river is a source of raw water contaminated by activities polluted indicated by activites a round the river. It has the potential of quartz sand which has been tested in the laboratory. contain SiO3 Which result for suak putat contains 93,04-98,45%, parit 67,96-98,76%,and tanjung harapan 96,95 % villages Test results of water processed quartz sand promontory villagcan hope to lower TDS parameters percentase with 6,67 % decline. For suak putat turbidity parameters can be reduce 16,82 %, nitrate 88,17 %. Nitrit 5% and colours parameters an increase 25,93 % but TDS do not change Tanjung harapan Village by test result for TDS parameters 6,67 %. Turbidity 7,04%, nitrate 80,69% and colour 15,43%, nitrat 98,1 %. and nitrit 75 %. Keyword: quartz sand, batanghari of river,pollutant